Diversification of the economy, tax revenue and sustainable growth in Nigeria - Adegbie, Festus Folajimi; Ajayi, Ademola; Aguguom, Theophilus Anaekenwa; Otitolaiye, Emmanuel Dare (International Journal of Innovative Research and Scientific Studies, 2023)
Economic diversification is a panacea for ensuring sustainable growth in developing countries. Studies have associated the problem of sustainable growth with the inability to broaden tax nets. The lack of economic diversification and the inadequate optimal utilization of tax revenue have deepened infrastructural deficits and slowed Nigeria’s sustainable growth. However, the extent to which diversification affects sustainable growth in Nigeria remains uncertain. Consequently, this study empirically examined the effect of economic diversification on Nigeria’s long-term growth. The ex-post facto research approach was adopted using time series data sourced from the Central Bank of Nigeria's statistical bulletin. The study covered 30 years from 1990 to 2020. Descriptive and inferential statistical tools were used in analyzing the data after carrying out unit root tests for stationarity to avoid obtaining invalid and unauthentic regression estimates. The study found that the GDP growth rate exhibited a positive and significant effect on sustainable growth, (AdjR2 = 0.581, F (6, 23) = 3.4299; p-value = 0.035). Furthermore, the study revealed that infrastructural expenditure had a positive but insignificant effect on sustainable growth (AdjR2 = 0.870; F (6, 23) = 0.037; p-value = 0.421). The study concluded that diversification had a positive effect on sustainable growth in Nigeria. Based on the results, the study recommended that Nigeria should maximize its resources and diversify the economy and ensure optimal utilization of tax revenue towards sustainable growth in Nigeria.